2011
DOI: 10.1164/rccm.201012-2090oc
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-controlled Clinical Trial of an Aerosolized β2-Agonist for Treatment of Acute Lung Injury

Abstract: Rationale: b 2 -Adrenergic receptor agonists accelerate resolution of pulmonary edema in experimental and clinical studies. Objectives: This clinical trial was designed to test the hypothesis that an aerosolized b 2 -agonist, albuterol, would improve clinical outcomes in patients with acute lung injury (ALI). Methods: We conducted a multicenter, randomized, placebocontrolled clinical trial in which 282 patients with ALI receiving mechanical ventilation were randomized to receive aerosolized albuterol (5 mg) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
166
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(170 citation statements)
references
References 41 publications
3
166
0
1
Order By: Relevance
“…Studies have shown if the initial pulmonary edema can be reduced by increasing alveolar fluid clearance or alveolar barrier function, inflammation and subsequent injury can also be lessened (8, 9). While a number of pharmacological approaches to modulate alveolar fluid clearance have been proposed in animal and human studies, including the use of β 2 -adrenergic receptor agonists, the results from several multi-center clinical trials have not shown significant benefit (10, 11). In light of this, we and others have tested whether gene therapy approaches may be alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown if the initial pulmonary edema can be reduced by increasing alveolar fluid clearance or alveolar barrier function, inflammation and subsequent injury can also be lessened (8, 9). While a number of pharmacological approaches to modulate alveolar fluid clearance have been proposed in animal and human studies, including the use of β 2 -adrenergic receptor agonists, the results from several multi-center clinical trials have not shown significant benefit (10, 11). In light of this, we and others have tested whether gene therapy approaches may be alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…It was ineffective as a treatment of pulmonary edema in two relatively recent multicenter clinical trials in critically ill patients either with acute lung injury (Matthay et al. 2011) or ARDS (Gao Smith et al. 2012) despite evidence of beneficial effect observed in cell culture as well as animal studies (Fronius 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival rates of ALI/ARDS are around 20-40% 4-7 . The prognosis of survival is better for mild ARDS as compared to severe ARDS with an intermediate risk for moderate ARDS (according to the ‘ Berlin definition ’) 1 .…”
Section: Introducing the Problemmentioning
confidence: 99%
“…Protein-based strategies have tested the administration of recombinant human proteins such as activated protein C (drotrecogin α), granulocyte macrophage colony stimulating factor (GM-CSF) and surfactant protein C based agents to ALI/ARDS patients 24-26 . Additional trials have used methylprednisolone, nitric oxide, β2-adrenergic receptor agonists (albuterol, salbutamol), and antioxidants (N-acetylcysteine) 7, 27-30 . All of these pharmacologic interventions were unable to demonstrate significant clinical efficacy (Table 1).…”
Section: Introducing the Problemmentioning
confidence: 99%